Highly Exfoliated Reduced Graphite Oxide Powders as Efficient Lubricant Oil Additives. Issue 22 (6th October 2016) - Li, Yingru; Zhao, Jun; Tang, Cheng; He, Yongyong; Wang, Yongfu; Chen, Ji; Mao, Junyuan; Zhou, Qinqin; Wang, Baoyuan; Wei, Fei; Luo, Jianbin; Shi, Gaoquan
Abstract : Highly exfoliated reduced graphite oxide (heRGO) is prepared by thermal reduction of crude graphite oxide (GO) powders with the assistance of KOH. By using the mixtures of KOH and GO with different weight ratios ( n ) as the starting materials, the resulting heRGO‐ n powders show different microstructures and lubrication properties. The optimized heRGO‐4 powders have an average particle size around 1 μm, a "loose book"‐like layered microstructure, and a large specific surface area of 829.5 m 2 g −1 . The unique microstructure and tiny particle sizes have made this graphene material to be an extraordinary high‐performance additive of poly(α‐olefin) lubricant oil (type 6, PAO‐6). By adding 0.5% (by weight, wt%) heRGO‐4, the coefficient of friction of PAO‐6 is decreased by 44% and the wear scar depth is reduced by more than 90%. The lubrication effect of heRGO‐4 is much superior to that of thermally reduced graphite oxide. Given its facile, cheap, and scalable preparation process, heRGO‐4 has a great potential for industrial applications. Abstract : A highly exfoliated reduced graphite oxide (heRGO) is prepared by thermal reduction of crude GO powders with the assistance of KOH. The heRGO has tiny particle sizes, unique lamellar porous microstructure, and a large specific surface area, making it to be an extraordinary high‐performance additive of poly(α‐olefin) lubricant oil (type 6).